Dose-response of Muscle Damaging Exercise on Cell-free DNA (Baltic Journal of Sport and Health Sciences, 2025)
Background: It has been observed that severe muscle damage induced by drop jumps has a significant effect on cell-free DNA (cfDNA) concentration. We hypothesized that a reduced volume of drop jumps would indicate a dose-dependent release of cfDNA.Methods: Seven participants (aged 21 ± 1.5 years) performed 25, and 4 participants (aged 22 ± 1.8 years) performed 10, intermittent drop jumps (DJs) at 20 s intervals (DJ-25 and DJ-10 groups). We measured cfDNA, creatine kinase (CK), lactate concentrations and delayed-onset muscle soreness (DOMS) before and at several time points up to 96 h after exercise.Results: There was a significant increase in plasma cfDNA levels immediately post-exercise in the DJ-25 group (p = 0.012). CK levels increased at 6, 12, 24 and 48 h post-exercise (p = 0.003, p < 0.001, p < 0.001, p = 003, accordingly) in the DJ-25 group. In the DJ-25 group only, DOMS values were increased at 12, 24 and 48 h post-exercise (p < 0.05).Conclusion: cfDNA is responsive to muscle-damaging exercise in a dose-dependent manner, as only 25 DJs resulted in an immediate increase in cfDNA concentrations after exercise, while 10 DJs were insufficient to elicit any change.Keywords: biomarker; eccentric exercise; muscle damage